The Artistic Links of Dora Pejačević and Svetislav Stančić Viewed Through the Stančić Legacy in the Library of the Academy of Music in Zagreb - Vilena Vrbanić (Arti Musices)
Just as interesting as the lives and works of prominent personalities from the history of Croatian music are the relations among and between these persons and the circle of people around them. Such things, on the one hand, tell of their networking, their influences on each other, the interweaving of their lives and artistic paths. On the other hand, they provide a wider picture of the persons themselves, about musical culture and the time in which they lived and worked. The aim of this paper is to shed light on the previously unknown artistic links between Dora Pejačević and Svetislav Stančić, respectable Croatian musicians and contemporaries, through the prism of his legacy in the Library of the Academy of Music in Zagreb. Of interest for this topic are boxes 1 and 2 in the archives, in which there are concert posters, programs and reviews of Stančić’s renderings of Dora’s works. Other testimonies to the way they worked together are the autograph of Dora’s Piano Sonata in A-flat major, Op. 57, and a message from her friend Olga Schulz-Granitz. Outside the Stančić Legacy, there is one more source that throws light on their relationship: the recording of a conversation broadcast as part of the Tragom glazbe series on the Third Program of Croatian Radio.